Step parameters and running economy of well-trained distance runners during high-intensity running - Tanji, F.; Enomoto, Y.; Nabekura, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2017)
This study investigated the relationships between running economy and various step parameters (ground contact time, step length and step frequency), as well as the effects of these relationships on differences in foot strike pattern at intensities ranging from below to above the lactate threshold in well-trained distance runners. Thirty-one male distance runners (20 middle-distance and 11 long-distance; age 19.5±1.2 years, height 171.7±4.5 cm, mass 57.6±3.5 kg, BMI 19.5±0.7) participated. Their seasonal best performance was 804.0±121.0 points, expressed as the IAAF score. Both running economy and step parameters were calculated for speeds of 15.0, 16.2 and 17.4 km·h-1, which corresponded to intensities below, equivalent to and above the lactate threshold, i.e. 93.2%±6.4%, 100.6%±6.9% and 108.1%±7.4%, respectively. As running speed increased, running economy, step length and step frequency increased, whereas the ground contact time decreased. A significant positive relationship was observed between ground contact time and running economy at an intensity above the lactate threshold (r=0.46; p<0.01). A significant positive relationship was observed between step length and running economy (r=0.54 and 0.52; p<0.01), and a negative relationship was observed between step frequency and running economy (r=-0.55 and -0.53; p<0.01) at intensities equivalent to and above the lactate threshold, respectively. Rear-foot strikers exhibited a shorter ground contact time than middle-foot strikers at intensities equivalent to and above the lactate threshold, whereas running economy exhibited no significant difference in terms of foot strike pattern. From the present results, it can be concluded that a shorter ground contact time enhances running economy; however, running economy is not related to the foot strike pattern at an intensity of 90%—110% of the lactate threshold